Living Fence: Ethnobotanical Study on Plant Utilization in Simeuue Island, Aceh Darussalam - Mohammad Fathi Royyani (INC- Islam Nusantara Center, 2019)
This is an ethnobotanical article that explains the use of plants by the people of Simeulue Island, Aceh to protect open agricultural fields (ladang) and rice fields (sawah) from free roaming-grazing livestock, particularly water buffalo, cows, and goats. In Simeulue, the livestock are released roaming free for food. In order to protect the open agricultural and rice fields, the people of Simeulue Island various species of plants are planted as living fences. The species selected are based on the local knowledge of plant morphology. The result of the current study indicates that 23 species of plants are implemented, in which the seeds and seedlings are found in the forests near the villages. In 2007, one foreign species known locally as ‘gamel’ (Gliricidia sepium; Fabaceae, the South American original) has been introduced for their easy planted, fast growing nature, and have been widely planted since. Kajian ini hendak melihat pemanfaatan tumbuhan sebagai pagar hidup yang melindungi lahan pertanian dan perkebunan dari hewan ternak yang dilepas-liarkan sehingga masuk ke lahan perkebunan masyarakat dan memakan tanaman. Untuk mengantisipasinya, masyarakat membuat pagar hidup yang berupa jenis-jenis pohon yang ditanam mengelilingi lahan. Melalui penelitian etnobotani diketahui bahwa masyarakat memilih jenis-jenis pohon yang dijadikan pagar hidup berdasarkan pengetahuan lokal terkait dengan tumbuhan. Jenis-jenis yang dipilih adalah jenis-jenis yang mudah tumbuh dan bisa bertahan dalam kerapatan. Dari hasil penelitian diketahui terdapat 23 jenis tumbuhan yang digunakan untuk pagar hidup. Dari jumlah tersebut sebagian besar tumbuh di hutan sekitar pemukiman mereka. Sejak tahun 2007 satu jenis baru, ‘gamel’ (Gliricidia sepium; Fabaceae, jenis asli Amerika Selatan) didatangkan dan ditanam menggantikan jenis lama. Tanaman baru ini lebih mudah ditanam, cepat tumbuh, dan kini sudah ditanam secara luas.